Facial Treatment With Botulinum Toxin Improves Attractiveness Rated by Self and Others, and Psychological Wellbeing. (December 2017) - Petrie, Taylor; Moore, Fhionna
Abstract : BACKGROUND: Treatment of dynamic facial lines with botulinum toxin has been shown to improve various measures of psychological wellbeing. OBJECTIVE: Here we sought to determine whether the positive effects of treatment on wellbeing occurred via improvements in attractiveness rated by self and others, using a pretreatment and post-treatment comparison experimental design. MATERIALS AND METHODS: We tested the effects of treatment on self-esteem, satisfaction with life, attractiveness rated by self and others in a sample of 32 Scottish women. Participants completed validated psychological measures of self-esteem, satisfaction with life, and self-perceived attractiveness pretreatment and 4 weeks post-treatment. Facial photographs with neutral expression of participants were rated for attractiveness by a group of raters pretreatment and 4 weeks post-treatment. RESULTS: Treatment significantly improved all measures (self-esteem, satisfaction with life, and attractiveness rated by self and others). Furthermore, self-rated attractiveness mediated the relationship between treatment and self-esteem. CONCLUSION: Treatment of dynamic facial lines with botulinum toxin significantly improves self-esteem and general life satisfaction. It also improves self-perceived attractiveness and attractiveness rated by others. The effects of treatment on self-esteem occur via the positive effects of treatment on self-perceived attractiveness. Our study is a carefully controlled analysis of the effects of treatment with botulinum toxin, using statistical analyses to show significant benefits of the treatment on psychology, wellbeing, and attractiveness as rated by self and others. This is further support for the psychological benefits of botulinum A facial therapy.